EFFECT OF MATERIAL SOURCING STRATEGIES ON ORGANIZATIONAL PERFORMANCE: A CASE OF JAMES FINLAY (KENYA) LIMITED - Korir, Philip Kiplangat; Kagiri, Dr. Assumpta (International Journal of Supply Chain Management, 2017)
Purpose: The general objective of the study was to investigate the effect of material sourcing strategies on organization performance Methodology: The study used descriptive research design through a cross-section survey within James Finlay (Kenya). The study targets three departments in the organization namely, procurement and supplies, finance and accounts, and executive management. Combined, the three departments have a population of 450 employees. Furthermore, the research used stratified sampling to narrow down from the 450 target population to 45 sample population. Primary and secondary quantitative and qualitative data were collected through questionnaire, interview, and online published documents. Quantitative data was processed using Statistical Package of Social Sciences (SPSS) version 21. Results: Results revealed JFL understand the importance of strategic material sourcing and it has invested considerably to ensure a streamlined supply chain. As a result, the study found a positive relationship between strategic material sourcing and organization performance. Unique Contribution to Theory Practice and Policy: strategic material sourcing is believed to streamlines the company's supply chain. A combination of selecting suppliers on merit basis, supplier relationship management, and supply chain partnership build a strong friendly relationship between the suppliers and the firm.